Piloting Low-Cost Transit Service Enhancements through Agency Collaboration. Issue 1 (January 2014) - Flint, Tanya; Ben-Amos, Ariel; Ellis, Patricia; Krykewycz, Gregory R.
In 2011, the City of Philadelphia, Pennsylvania; the Southeastern Pennsylvania Transportation Authority (SEPTA); and the Delaware Valley Regional Planning Commission (DVRPC) launched the Route 47 Service Enhancement Pilot Project. This project was conceived within the framework of the Transit First Committee. The pilot presented an opportunity to evaluate the effectiveness of low-cost operational initiatives that might have the ability to improve transit services in dense, urban environments. These strategies included bus stop consolidation, farside stop placement, and the switch from a time point–based scheduling system to a headway-based scheduling system. This joint initiative served as a test of the potential to build community support for a pilot, the impact of the interventions themselves, and the ability of the Transit First Committee to work together collaboratively. Although the pilot initiative did not deliver the time savings expected, the process provided important lessons for the city, SEPTA, and DVRPC that are applicable for other transit agencies operating in similar geographic, political, and economic environments. The results of the collaborative process necessary to get the pilot in motion helped to reconnect the city and SEPTA after years of distrust and discord. The initiatives piloted were scrutinized through data analysis, which provided not only an understanding of the impacts but also an awareness of operational performance issues. Ultimately, this extensive data analysis supported decision making, fostered agreement between stakeholders, and developed trust within the community.